Dimmable High Power LED Driver Using Fuzzy Logic Controller - Rizky Fatur Rochman; Eka Prasetyono; Rachma Prilian Eviningsih (IJITEE (International Journal of Information Technology and Electrical Engineering), 2021)
The use of lighting loads is one of the crucial matters which increases every year. The increasing use then leads to the development of brighter and longer-lasting sources. In addition, the conventional use of lighting loads today, which only emit light at its maximum intensity, does not allow the consumers to adjust the brightness level as needed. Consequently, this condition may cause energy wastage. The LED lighting system is gaining popularity as it is widely used in a wide range of applications. The advantages of LEDs, such as its compact size and varied lamp colors, replace conventional lighting sources. The linear setting of the driver topology using the flyback converter was aimed to control the LEDs with a constant current in order to adjust the variation of the LED light intensity. The closed-loop driver circuit with flyback converter topology was designed as an LED driver with a given load specification from the LED string. A dimmable feature was included for adjusting the intensity of the light produced by the LEDs. Eventually, the fuzzy logic controller (FLC) method was applied to the integrated change setting to obtain a dynamic response.